A Middle School Program to Prevent E-Cigarette Use: A Pilot Study of "CATCH My Breath" - Kelder, Steven H; Mantey, Dale S; Van Dusen, Duncan; Case, Kathleen; Haas, Alexandra; Springer, Andrew E (Public health reports (1974), 2020)
From 2017 to 2018, electronic cigarette (e-cigarette) use increased 78% among high school students and 48% among middle school students in the United States. However, few e-cigarette prevention interventions have been evaluated. We determined the feasibility and initial effectiveness of "CATCH My Breath," an e-cigarette prevention program, among a sample of middle schools in central Texas. Twelve middle schools in Texas (6 intervention schools and 6 control schools) participated in the CATCH My Breath pilot program during 2016-2017. CATCH My Breath is rooted in social cognitive theory, consists of 4 interactive in-class modules, and is collaboratively administered via classroom and physical education teachers, student-peer leaders, and social messaging (eg, school posters). We collected 3 waves of data: baseline (January 2017), 4-month follow-up (May 2017), and 16-month follow-up (May 2018). Using school as the unit of analysis, we tested a repeated cross-sectional, condition-by-time interaction on e-cigarette ever use, psychosocial determinants of use, and other tobacco use behaviors. Analyses controlled for school-level sociodemographic characteristics (eg, sex, race/ethnicity, and percentage of students eligible for free or reduced-price lunch). From baseline to 16-month follow-up, increases in ever e-cigarette use prevalence were significantly lower among intervention schools (2.8%-4.9%) than among control schools (2.7%-8.9%), controlling for covariates ( = .01). Intervention schools also had significantly greater improvements in e-cigarette knowledge (β = 0.71; 95% confidence interval [CI], 0.21-1.21; = .008) and perceived positive outcomes (β = -0.12; 95% CI, -0.23 to -0.02; = .02) than control schools, controlling for covariates from baseline to 16-month follow-up. Ever e-cigarette use was lower among middle schools that implemented the CATCH My Breath program than among those that did not. Replication of findings among a larger sample of schools, using a group-randomized, longitudinal study design and a longer follow-up period, is needed.